2014
DOI: 10.1371/journal.pone.0086859
|View full text |Cite
|
Sign up to set email alerts
|

Peace-Making in Marsupials: The First Study in the Red-Necked Wallaby (Macropus rufogriseus)

Abstract: The issue of reconciliation has been widely investigated in many eutherian mammal species. Nevertheless, no data are available for marsupial mammals. Indeed, the majority of reports focus on group dynamics from an ecological and reproductive perspective, but no study has investigated them from a social point of view. We observed the red-necked wallaby colony (Macropus rufogriseus) hosted at the Tierparc Zoo Berlin (Germany) and collected data on aggressive and post-conflict interactions between group members. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…First‐affiliative behaviors occurred earlier after aggressions (on average within the first 3 min) than in control periods. Similarly, conciliations reported in ravens ( Corvus corax ), red‐necked wallabies ( Macropus rufogriseus ), and spotted hyenas ( Crocuta crocuta ) occurred within the first 2–5 min after a conflict (Cordoni & Norscia, ; Fraser & Bugnyar, ; Wahaj et al, ). In a group of captive bottlenose dolphins, the affiliation between former opponents occurred mostly within 1 min after aggression (Yamamoto et al, ).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…First‐affiliative behaviors occurred earlier after aggressions (on average within the first 3 min) than in control periods. Similarly, conciliations reported in ravens ( Corvus corax ), red‐necked wallabies ( Macropus rufogriseus ), and spotted hyenas ( Crocuta crocuta ) occurred within the first 2–5 min after a conflict (Cordoni & Norscia, ; Fraser & Bugnyar, ; Wahaj et al, ). In a group of captive bottlenose dolphins, the affiliation between former opponents occurred mostly within 1 min after aggression (Yamamoto et al, ).…”
Section: Discussionmentioning
confidence: 78%
“…However, it is important to note that the value of the CCT found in the present study must be considered with caution due to the small number of PC-MC observations compared to other studies, which used more than 100 pairs of PC-MC observations for the analysis of reconciliation tendencies (e.g., Cordoni & Norscia, 2014;Cozzi et al, 2010;Palagi, Paoli, & Tarli, 2004).…”
Section: Conflict Resolutionmentioning
confidence: 73%
See 2 more Smart Citations
“…As this brief overview illustrates, the vast majority of reconciliation research has focused on primates (see Romero & Aureli, 2007, Table 1). Though limited by comparison, systematic studies of reconciliation in non-primate animal societies, including canids (Cools, Van Hout, & Nelissen, 2008;Cordoni & Palagi, 2008), cetaceans (Weaver, 2003), marsupials (Cordoni & Norscia, 2014), hyenas (Wahaj, Guse, & Holekamp, 2001), domestic horses (Cozzi, Sighieri, Gazzano, Nicol, & Baragli, 2010) and goats (Schino, 1998), corvids (Fraser & Bugnyar, 2011), and fish (Bshary & Würth, 2001) have revealed that post-conflict affiliative behaviours are by no means limited to primate or even mammalian taxa, and have provided new insights to the VHR. For example, reconciliation is thought to be largely absent in cooperative breeders because valuable partners (i.e., the breeding pair) rarely engage in aggression (Logan, Emery, & Clayton, 2012;Seed, Clayton, & Emery, 2007).…”
Section: Introductionmentioning
confidence: 99%